English for Academic Purposes at Swedish universities (Ibérica, 2011)
In a parallel-language environment the use of textbooks in English in courses otherwise in the local language is naturalized and not widely discussed or questioned. The aim of this study was to elicit the attitudes and syllabus infrastructure that underlie the practice. A large-scale survey was carried out and answers were obtained from over 20% of teachers at Swedish universities. Results confirmed that a majority regarded English as important during and/or after university studies and showed that they considered the use of Englishlanguage textbooks as providing a useful opportunity for incidental language learning. In strong contrast to the situation in a content and language integrated learning environment, only a small minority of courses were reported to have any specified learning outcome related to English. Open answers showed awareness of the benefits and risks of parallel-language practices, but no interest in making aims explicit. In our view, there is no contradiction between incidental learning and explicit aims, and course aims which remain implicit make rational planning and constructive alignment more difficult. They also inhibit discussion of appropriate methodology.